2022
DOI: 10.3389/fgene.2022.990326
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of cuproptosis-related long noncoding RNA immune infiltration and prediction of prognosis in patients with bladder cancer

Abstract: Background: Bladder cancer (BCa), among the world’s most common malignant tumors in the urinary system, has a high morbidity and mortality. Though cuproptosis is a new type of cell death mediated by lipoylated tricarboxylic acid (TCA) cycle proteins, the role of cuproptosis-related long noncoding RNAs (crlncRNAs) in bladder tumors awaits further elucidation. In this paper, we tried to explore how important crlncRNAs are for BCa.Methods: The crlncRNAs were first obtained through Pearson correlation analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…Cuproptosis is a novel type of programmed cell death and is different from other known death forms, including apoptosis, ferroptosis, and necroptosis. A previous study showed that cuproptosis is involved in the development and progression of malignancies ( 22 ). As cuproptosis is a newly discovered type of programmed cell death, there are limited data and studies related to its clinical value in BLCA.…”
Section: Discussionmentioning
confidence: 99%
“…Cuproptosis is a novel type of programmed cell death and is different from other known death forms, including apoptosis, ferroptosis, and necroptosis. A previous study showed that cuproptosis is involved in the development and progression of malignancies ( 22 ). As cuproptosis is a newly discovered type of programmed cell death, there are limited data and studies related to its clinical value in BLCA.…”
Section: Discussionmentioning
confidence: 99%
“…Copper can be involved in angiogenesis, tumor growth and metastasis, and cancer cells can adapt to adverse microenvironment by regulating copper metabolism [18]. CRLs can be used to predict the prognosis and immune microenvironment of patients suffering from bladder cancer, which high risk patients were enriched in several immune-related pathways such as cell proliferation, nucleotide metabolism, and in ammatory immune response [19]. The cuproptosis is closely related to immune system [20].…”
Section: Discussionmentioning
confidence: 99%
“…Although recent studies have also investigated cuproptosisrelated lncRNAs in the prognosis and immunity of BLCA (Zhang et al, 2022), research in this area needs to be continuously explored to improve the treatment outcome and prognosis of BLCA patients. Therefore, in our research, we built a prognostic model of cuproptosis-related lncRNAs in BLCA and assessed the model accuracy while studying the immune infiltration, drug sensitivity and immune checkpoint analysis of highly mutated genes in the high-risk group to provide a scientifically useful basis for further studies.…”
Section: Introductionmentioning
confidence: 99%